Perancangan Sistem Informasi Jual Beli Properti “BWR Property” Berbasis Web Terintegrasi - Putra, I Wayan Weda Adi; Januarta, I Komang Bagus; Romeo, Made (Journal Informatics Nivedita, 2026)
The high market demand for residential and commercial properties today requires a fast, transparent, and easily accessible information platform for the wider community. Therefore, this research was conducted to design and develop "BWR Property", a web-based property marketing and rental platform. Unlike typical e-commerce, this application implements a direct communication route innovation (Direct Agent Link). Through this mechanism, the transaction process is bridged personally between prospective consumers and the assigned property agents. Technically, the system was built using a Full-Stack architecture and developed based on the Waterfall model of the System Development Life Cycle (SDLC) method. System testing was then executed using the Black Box Testing technique. Out of the five main functional testing scenarios, the system successfully achieved a 100% feasibility rate with a data loading speed of under 2 seconds. In conclusion, this research successfully produced a responsive property portal capable of facilitating secure interpersonal negotiations, making it an ideal solution for large-scale property inventory digitalization.